PENERAPAN KETENTUAN TENTANG RESTORATIVE JUSTICE PADA TINDAK PIDANA KEKERAASAN DALAM RUMAH TANGGA (STUDI PUTUSAN NO 56/PID.SUS/PN BDW): Implementation Of Restorative Justice Provisions In Cases Of Domestic Violence Crimes (Verdict Study No56/Pid.Sus/PNBdw) - Vinsky Nayla Chairunnisa Siregar; Abdul Ficar Hadjar (AMICUS CURIAE, 2025)
Restorative Justice is an alternative method for resolving criminal acts, including complaint offenses as seen in Decision No. 56/PidSus/2020/PN BDW. The identification of the problem in this research is whether the application of Restorative Justice in cases of domestic violence complies with Law No. 23 of 2004 and whether the judge's decision aligns with the applicable laws. The research was conducted using a normative, descriptive-analytical approach, utilizing secondary data. Based on the research results and conclusions, it is concluded that the application of restorative justice in this case follows the mechanism regulated in the Director General of General Courts Decree No.1691/DJU/SK/PS.00/12/2020. Although a peace agreement and withdrawal of complaints occurred, this does not eliminate the criminal liability of the defendant. The judge also decided that the defendant does not need to serve a prison sentence. However, the researcher suggests that peace in the concept of restorative justice should not only function as a mitigating factor but also as a reason to abolish punishment and regulate the legal settlement of domestic violence criminal cases more clearly. If domestic violence cases do not meet the criteria for restorative justice, the formalistic criminal justice system may be applied.